2001
DOI: 10.1006/jcis.2001.7908
|View full text |Cite
|
Sign up to set email alerts
|

pH-Dependent Aggregation Behavior of a Sugar-Amine Gemini Surfactant in Water: Vesicles, Micelles, and Monolayers of Hexane-1,6-bis(hexadecyl-1′-deoxyglucitylamine)

Abstract: The pH-dependent aggregation behavior of one representative of a recently described series of sugar-amine gemini surfactants has been investigated. The surface tension (γ ) and turbidity of hexane-1,6-bis(hexadecyl-1 -deoxyglucitylamine) drop steeply between pH 5.5 and 4.0, consistent with a vesicle-to-micelle transition. The critical micelle concentration (cmc) at low pH (3.0) was determined by surface tension measurements to be 1 × 10 −3 M. This value is high, as γ is at the cmc (57 mN m −1 ). The area per h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
2
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 25 publications
3
57
2
1
Order By: Relevance
“…Several physico-chemical properties of the same system are reported by Bergsma et al [9]. The molecular structure of the surfactants used in those studies is shown in Figure 1.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations
“…Several physico-chemical properties of the same system are reported by Bergsma et al [9]. The molecular structure of the surfactants used in those studies is shown in Figure 1.…”
Section: Introductionsupporting
confidence: 52%
“…If the glucitol groups had not been present, this might have even led to a maximum in φ 0 as is, e.g., observed for gemini surfactants of type ( [28,4]. Due to the very low critical association concentration of the glucitol amine surfactant, also reflected in the formation of vesicles [9], no experimental cmc data is available for the present system. Instead of changing the pH to change the electrostatic interactions, one can also change the ionic strength of the solution by adding salt to the solution.…”
Section: Effects Of Spacer Length and Ionic Strengthmentioning
confidence: 79%
See 2 more Smart Citations
“…Molecular self-assembly is also caused by the polymers responding to stimuli, resulting in the construction of high-dimensional structures of the polymers. Stimuli inducing self-assembly of the polymers include pH [17,18], temperature [19][20][21][22], and pressure [23][24][25][26]. Recently, it has been reported that chemical reactions inducing self-assembly of the polymers; the oxidation [27], reduction [28][29][30], and disproportionation [31,32] of stable nitroxyl radicals supported on the side chains of a block copolymer, promote the micellization of the copolymer to provide micelles that function as oxidants and reductants.…”
Section: Introductionmentioning
confidence: 99%